The universality of trust? - Batt, Peter (Massey University, 2001)
Emperical evidence is presented which suggests that trust is more important in facilitating exchange in transitional economies than industrial economies. Furthermore, the various item measures that have been employed to evaluate trust in Europe, North America, Australia and Japan, fail to accurately describe the construct among small farmers in a developing country. While further studies are necessary to develop a more robust measure of trust, in the context of small business, trust between organisations and individual's is difficult to differentiate.